2003
DOI: 10.5012/bkcs.2003.24.8.1102
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Induced Multipoles on the Fifth-order Raman Response

Abstract: In our previous work we developed the Finite Field method in order to calculate the fifth-order Raman response. The method was applied to calculate various polarization components of the two-dimensional response of liquid CS2. So far, all calculations relied on the dipole-induced dipole. Accurate time-dependent density functional theory calculations have shown that this model has big discrepancies, when molecules are close together as in the liquid. We now report results of investigations on the importance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2006
2006

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Without at least one of these two sources, no fifth-order Raman signal can exist. It was expected that in most liquids each of these sources will contribute to the signal, and early work in the field indicated it should be possible to separate the effects of the two contributions. , Over the years, intense theoretical efforts have used a variety of approaches to simulate the fifth-order Raman response of various systems, including multimode Brownian oscillator models, ,, harmonic oscillator models, normal-mode theory, molecular dynamics simulations, hydrodynamic theory, the generalized Langevin equation, classical time correlation functions, and finite-field molecular dynamics simulations. In several cases, this has required the development of new theories and computational approaches, with previous theories having proved inadequate at properly describing the liquid state. Collectively, the theoretical work in this area has demonstrated that the fifth-order Raman response is very sensitive to the details of the intermolecular potential and treatment of the liquid dynamics.…”
Section: Introductionmentioning
confidence: 99%
“…Without at least one of these two sources, no fifth-order Raman signal can exist. It was expected that in most liquids each of these sources will contribute to the signal, and early work in the field indicated it should be possible to separate the effects of the two contributions. , Over the years, intense theoretical efforts have used a variety of approaches to simulate the fifth-order Raman response of various systems, including multimode Brownian oscillator models, ,, harmonic oscillator models, normal-mode theory, molecular dynamics simulations, hydrodynamic theory, the generalized Langevin equation, classical time correlation functions, and finite-field molecular dynamics simulations. In several cases, this has required the development of new theories and computational approaches, with previous theories having proved inadequate at properly describing the liquid state. Collectively, the theoretical work in this area has demonstrated that the fifth-order Raman response is very sensitive to the details of the intermolecular potential and treatment of the liquid dynamics.…”
Section: Introductionmentioning
confidence: 99%